Accuracy of Voltage Signal Measurement During Radiofrequency Delivery Through the SMARTTOUCH Catheter. (8th November 2016) - SAFAVI‐NAEINI, PAYAM; ZAFAR‐AWAN, DREEMA; ZHU, HONGJIAN; ZABLAH, GERARDO; GANAPATHY, ANAND V.; RASEKH, ABDI; SAEED, MOHAMMAD; RAZAVI, JOANNA ESTHER MOLINA; RAZAVI, MEHDI
Voltage Measurement During Radiofrequency Delivery: Introduction: Current methods for measuring voltage during radiofrequency (RF) ablation (RFA) necessitate turning off the ablation catheter. If voltage could be accurately read without signal attenuation during RFA, turning off the catheter would be unnecessary, allowing continuous ablation. We evaluated the accuracy of the Thermocool SMARTTOUCH catheter for measuring voltage while RF traverses the catheter. Methods and Results: We studied 26 patients undergoing RFA for arrhythmias. A 7.5F SMARTTOUCH catheter was used for sensing voltage and performing RFA. Data were collected from the Carto‐3 3‐dimensional mapping system. Voltages were measured during ablation (RF‐ON) and immediately before or after ablation (RF‐OFF). In evaluating the accuracy of RF‐ON measurements, we utilized the RF‐OFF measure as the gold standard. We measured 465 voltage signals. The median values were 0.2900 and 0.3100 for RF‐ON and RF‐OFF, respectively. Wilcoxon signed rank testing showed no significant difference in these values (P = 0.608). The intraclass correlation coefficient (ICC) was 0.96, indicating that voltage measurements were similarly accurate during RF‐OFF versus RF‐ON. Five patients had baseline atrial fibrillation (AF), for whom 82 ablation points were measured; 383 additional ablation points were measured for the remaining patients. The voltages measured during RF‐ON versus RF‐OFF were similar in the presence of AF (P = 0.800) versus non‐AF rhythm (P = 0.456) (ICC, 0.96 for both). Conclusion: Voltage signal measurement was similarly accurate during RF‐ON versus RF‐OFF independent of baseline rhythm. Physicians should consider not turning off the SMARTTOUCH ablation catheter when measuring voltage during RFA.